Evaluating the effectiveness of ATI-RTC XI learning sites and schools for practical agriculture in Region XI - Gordo, Gilbert M.; Importante, Gilbert A.; Jadraque, Angelo E.; Castillo, Rey A.; Felisarta, Willam M.; Satorre, Robert C. (2019)
The Department of Agriculture-Agricultural Training Institute is continually keeping up with the challenges on the implementation of its extension programs. This study elaborates on the effectiveness of the Learning Sites (LS) and School for Practical Agriculture (SPA) in delivering technologies to farmers. Mixed methods approach was used to generate qualitative and quantitative measures. These included the conduct of focus group discussion, survey, and field visits. There were 10 participants in the FGD and 154 respondents for the survey. Regression analysis was used to explain the determinants of the effectiveness of established program objectives. Return on investment and value for money estimates showed that farmers' income increased. Moreover, the sufficiency of inputs and conduciveness of the facilities were found to directly relate to program success. Consequently the implementation of LS and SPA is deemed effective and sustainable.
Keywords: Department of Agriculture-Agricultural Training Institute; Learning sites; Practical agriculture